Adult onset idiopathic torsion dystonia is excluded from the DYT 1 region (9q34) in a Swedish family. Issue 2 (August 1995) - Holmgren, G; Ozelius, L; Forsgren, L; Almay, B G; Holmberg, M; Kramer, P; Fahn, S; Breakefield, X O
Abstract : A gene (DYT1) for early onset idiopathic torsion dystonia was mapped to chromosome 9q34 in non-Jewish and Jewish families. The DYT1 gene region has been excluded in other families with adult onset and cervical or cranial onset idiopathic torsion dystonia from the United States, Great Britain, and France. The role of DYT1 in a Swedish family with adult onset idiopathic torsion dystonia in four generations was examined. The disease seems to be inherited in an autosomal dominant mode with reduced penetrance in this family. There were 10 affected family members, with a mean age of onset of 27 (range 18 to 50) years. The disease showed variable expression, with focal, multifocal, and generalised forms of dystonia in different family members. Genetic analysis excluded the chromosomal region containing the DYT1 locus as being responsible for dystonia in this family.